Barriers and facilitators in implementing a pilot, pragmatic, telemedicine-delivered healthy lifestyle program for obesity management in a rural, academic obesity clinic - Batsis, John A.; McClure, Auden C.; Weintraub, Aaron B.; Sette, Diane; Rotenberg, Sivan; Stevens, Courtney J.; Gilbert-Diamond, Diane; Kotz, David F.; Bartels, Stephen J.; Cook, Summer B.; Rothstein, Richard I. (Implementation science communications, 2020)
Purpose Few evidence-based strategies are specifically tailored for disparity populations such as rural adults. Two-way video-conferencing using telemedicine can potentially surmount geographic barriers that impede participation in high-intensity treatment programs offering frequent visits to clinic facilities. We aimed to understand barriers and facilitators of implementing a telemedicine-delivered tertiary-care, rural academic weight-loss program for the management of obesity. Methods A single-arm study of a 16-week, weight-loss pilot evaluated barriers and facilitators to program participation and exploratory measures of program adoption and staff confidence in implementation and intervention delivery. A program was delivered using video-conferencing within an existing clinical infrastructure. Elements of Consolidated Framework for Implementation Research (CFIR) provided a basis for assessing intervention characteristics, inner and outer settings, and individual characteristics using surveys and semi-structured interviews. We evaluated elements of the RE-AIM model (reach, adoption) to assess staff barriers to success for future scalability. Findings There were 27 patients and 8 staff completing measures. Using CFIR, the intervention was valuable from a patient participant standpoint; staff equally had positive feelings about using telemedicine as useful for patient care. The RE-AIM framework demonstrated limited reach but willingness to adopt was above average. A significant barrier limiting sustainability was physical space for intervention delivery and privacy and dedicated resources for staff. Scheduling stressors were also a challenge in its implementation. Conclusions The need to engage staff, enhance organizational culture, and increase reach are major factors for rural health obesity clinics to enhance sustainability of using telemedicine for the management of obesity. Trial registration Clinicaltrials.gov NCT03309787 . Registered on 16 October 2017.